2020
DOI: 10.1016/j.ajhg.2020.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Sequencing for Newborn Screening: Results of the NC NEXUS Project

Abstract: Newborn screening (NBS) was established as a public health program in the 1960s and is crucial for facilitating detection of certain medical conditions in which early intervention can prevent serious, life-threatening health problems. Genomic sequencing can potentially expand the screening for rare hereditary disorders, but many questions surround its possible use for this purpose. We examined the use of exome sequencing (ES) for NBS in the North Carolina Newborn Exome Sequencing for Universal Screening (NC NE… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 103 publications
(93 reference statements)
1
63
0
Order By: Relevance
“…WES was therefore concluded to be insufficiently sensitive or specific as a general primary NBS test for IEM. The NC NEXUS study was performed in a smaller cohort and found similar results (54).…”
Section: Sensitivity/specificity Tradeoffs In Diagnosis Vs Screeningmentioning
confidence: 62%
See 3 more Smart Citations
“…WES was therefore concluded to be insufficiently sensitive or specific as a general primary NBS test for IEM. The NC NEXUS study was performed in a smaller cohort and found similar results (54).…”
Section: Sensitivity/specificity Tradeoffs In Diagnosis Vs Screeningmentioning
confidence: 62%
“…Analysis was blinded to phenotype, and analyzed genes included those with childhood-onset medically actionable disorders (NBS-NGS, 466 genes, all subjects) and those with diagnostic findings (affected subjects, additional indication-based genes analyzed). This project included randomization to an arm in which parents could decide whether to learn additional information from the genomic analysis including low or no actionability childhood-onset conditions, high actionability adult-onset conditions, and carrier status for recessive disorders ( 54 ). The NBSeq project performed exome sequencing retrospectively on DNA obtained from dried blood spots of cases with known IEM diagnosed through conventional newborn screening in California.…”
Section: Whole Exome and Whole Genome Sequencing In Disease Screeningmentioning
confidence: 99%
See 2 more Smart Citations
“…It is proposed that the primary benefits of early genetic diagnosis in these patients include both the rapid implementation of targeted interventions that may decrease morbidity, as well as the rapid identification of likely futile intensive care in the course of what may otherwise be a protracted diagnostic approach during, which parents may experience "inappropriate hope" or "needless guilt." Meanwhile, secondary benefits may include guiding parents regarding the risk of recurrence in future children as well as possible overall healthcare cost reductions [1,27].…”
Section: Next-generation Sequencing For Diagnostic Evaluation Of Critically Ill Newbornsmentioning
confidence: 99%